Investigation and experiment of radar systems in unmanned aerial vehicles - Erwin Brian Jegaraj (2016)
In recent times, there is a growing interest in radars used by Unmanned Aerial Vehicles (UAV). These radars in UAVs are used for a variety purposes such as surveillance & reconnaissance, interferometry, foliage penetration, environmental monitoring, moving target indication, etc. However, the two most common usages are to measure distance and generate a Synthetic Aperture Radar (SAR) image. Thus this report begins by discussing the fundamentals of a radar, in particular a Frequency Modulated Continuous Wave (FMCW) radar system and how a synthetic aperture can be generated with a small antenna thereby creating a 2-Dimensional image with a resolution comparable with one generated by a large antenna. Next, it highlights some of the important modules in a FMCW radar system and steps taken to improve the accuracy of the system. Finally, the report concludes by deliberating factors that affected the range calculation in both a controlled and uncontrolled environment.